Initial Development of a Patient Reported Experience Measure for Older Adults Attending the Emergency Department: Part I—Interviews with Service Users - Graham, B.; Smith, J.E.; Nelmes, P.; Squire, R.; Latour, Jos (2023)
Older adults are a major Emergency Department (ED) user group who may be especially vulnerable to the consequences of crowding and sub-optimal care. Patient experience is a critical component of high-quality ED care and has previously been conceptualised using a framework focusing on patients’ needs. This study aimed to explore the experiences of older adults attending the ED in relation to the existing needs-based framework. Semi-structured interviews were conducted during an emergency care episode with 24 participants aged over 65 years in a United Kingdom ED with an annual census ~100,000. Questions exploring patient experiences of care confirmed that meeting the communication, care, waiting, physical, and environmental needs were prominent determinants of experience for older adults. A further analytical theme emerged which did not align to the existing framework, focused on ‘team attitudes and values’. This study builds on existing knowledge relating to the experience of older adults in the ED. In addition, data will also contribute to the generation of candidate items for the development of a patient reported experience measure for older adults attending the ED.